Some aspects of Space instrument engineering in Ukraine in ‘70s-‘90s of the 20th cent. - Sukhoterina, L. I.; Yampolskyi, Yu. R.; Bondar, V. I. (History of science and technology, 2013)
In the article discusses the contribution of scientists cathedra of radiodevices Odessa Polytechnic University in the design, development and manufacture of scientific instruments for the study of the physical characteristics of the interplanetary plasma.